ON THE RELATIONSHIP OF TRADITIONAL AND NON-TRADITIONAL LIPID PARAMETERS WITH THE RISK OF PREDIABETES AND TYPE 2 DIABETES MELLITUS IN PATIENTS WITH CORONARY HEART DISEASE IN THE UZBEK POPULATION - Narimova G. J.; Kulimova G. A. (American Journals Publishing, 2025)
The aim of this study was to compare the TG/HDL relationship andother non-traditional lipid parameters with pre-DM and T2DM in the Uzbek population of patients with coronary heart disease, and to test the association of high TG/HDL levels based on gender-specific thresholds with pre-DM and T2DM.Material and methods of research.We studied the age characteristics of the surveyed rural population of Tuprok-Kal district in the Khorezm region. There were 132 women and 107 men. Of the 239 individuals, 100 patients with carbohydrate metabolism disorders and type 2 diabetes were identified. Among the 100 individuals with identified carbohydrate metabolism disorders, 46 patients with coronary heart disease were identified.The following methods were used in the population survey: epidemiological, clinical, biochemical, instrumental and statistical.Study results. Significant differences were observed in a number of parameters compared to the group without NMD. Significant differences were found in family history of type 2 diabetes, systolic blood pressure, diastolic blood pressure, smoking, alcohol abuse, and hypertension compared to all studied patient groups (p < 0.005). Patients with IFG+IGT and type 2 diabetes demonstrated the highest significance of differences in family history of type 2 diabetes, p < 0.0001.Regarding biochemical parameters, it was revealed that the reliability of differences in the lipid spectrum was detected in patients with type 2 diabetes (p < 0.005), while in the other groups such differences were not detected.
Keywords: Type 2 diabetes mellitus, coronary heart disease, correlation.